Abandono familiar y su incidencia en la depresión de un adulto mayor de 77 años del Cantón Caluma - Rea Barragán, María Belén (2023)
The present case study was carried out on an adult over 77 years of age who resides in the canton with the objective of establishing the incidence of family abandonment in depression in the elderly. The symptoms observed include a significant loss of concentration, persistent sadness and a series. of somatic problems, such as increased sleep and decreased appetite. Through diagnostic evaluations, a diagnosis of major depressive disorder was reached according to DSM-5 criteria. To carry out this complex clinical picture, a comprehensive therapeutic approach was implemented focused on modifying negative thinking patterns, with the goal of improving both mental and physical health. Given the patient's circumstances, who lack close family members, recommendations are given for distant family members who may be involved, in addition to seeking community support. In addition, the technical sheet was used as a tool to systematically organize and document the relevant data of the case, thus illustrating the incidence of family abandonment in depression in the context of an older adult.